Numerical investigation of the effect of the injection angle on the spray structures of an air-blast atomizer. Issue 5 (23rd November 2020) - Chen, Sheng; Xing, Yuming; Liu, Xin; Zhao, Liang
Abstract : Purpose: The purpose of this study is to investigate the effect of the injection angle α on the spray structures of an air-blast atomizer and help enhance the understanding of droplet-gas mixing process in such atomizers in the engineering domain. Design/methodology/approach: The phenomena in the air-blast atomizer were numerically modelled using the computational fluid dynamics software Fluent 17.2. The Euler-Lagrange approach was applied to model the droplet tracking and droplet-gas interaction in studied cases. The standard k-ε model was used to simulate the turbulent flow. A model with a modified drag coefficient was used to consider the effects of the bending of the liquid column and its penetration in the primary breakup region. The Kelvin-Helmholtz, Rayleigh-Taylor model was applied to consider the secondary breakup of the droplets. Findings: The basic spatial distribution and spray structures of the droplets corresponding to the angled liquid jet ( α = 60°) were similar to those reported in liquid jets injected transversely into a gaseous crossflow studies. The injection angle α did not considerably influence the averaged Sauter to mean diameter (SMD) of the cross-sections. However, the spray structures pertaining to α = 30°, α = 60° and α = 90° were considerably different. In the case of the atomizer with multiple injections, a "collision region" was observed at α = 60° and characterized by a higher ci and larger averaged SMD in the central parts of the cross-sections. Originality/value: The injection angle α is a key design parameter for air-blast atomizers. The findings of this study can help enhance the understanding of the droplet-gas mixing process in air-blast atomizers. Engineers who design air-blast atomizers and face new challenges in the process can refer to the presented findings to obtain the desired atomization performance. The code has been validated and can be used in the engineering design process of the gas-liquid jet atomizer.